Antibiotic Resistance Genes in Lemur Gut and Soil Microbiota Along a Gradient of Anthropogenic Disturbance - Bornbusch, Sally L.; Drea, Christine M. (Frontiers in Ecology and Evolution, 2021)
The overuse of man-made antibiotics has facilitated the global propagation of antibiotic resistance genes in animals, across natural and anthropogenically disturbed environments. Although antibiotic treatment is the most well-studied route by which resistance genes can develop and spread within host-associated microbiota, resistomes also can be acquired or enriched via more indirect routes, such as via transmission between hosts or via contact with antibiotic-contaminated matter within the environment. Relatively little is known about the impacts of anthropogenic disturbance on reservoirs of resistance genes in wildlife and their environments. We therefore tested for (a) antibiotic resistance genes in primate hosts experiencing different severities and types of anthropogenic disturbance (i.e., non-wildlife animal presence, human presence, direct human contact, and antibiotic treatment), and (b) covariation between host-associated and environmental resistomes. We used shotgun metagenomic sequencing of ring-tailed lemur (Lemur catta) gut resistomes and associated soil resistomes sampled from up to 10 sites: seven in the wilderness of Madagascar and three in captivity in Madagascar or the U.S. We found that, compared to wild lemurs, captive lemurs harbored greater abundances of resistance genes, but not necessarily more diverse resistomes. Abundances of resistance genes were positively correlated with our assessments of anthropogenic disturbance, a pattern that was robust across all ten lemur populations. The composition of lemur resistomes was site-specific and the types of resistance genes reflected antibiotic usage in the country of origin, such as vancomycin use in Madagascar. We found support for multiple routes of ARG enrichment (e.g., via human contact, antibiotic treatment, and environmental acquisition) that differed across lemur populations, but could result in similar degrees of enrichment. Soil resistomes varied across natural habitats in Madagascar and, at sites with greater anthropogenic disturbance, lemurs and soil resistomes covaried. As one of the broadest, single-species investigations of wildlife resistomes to date, we show that the transmission and enrichment of antibiotic resistance genes varies across environments, thereby adding to the mounting evidence that the resistance crisis extends outside of traditional clinical settings.